Ultrafast electronic spectroscopy on the coupling of Stranski-Krastanov and submonolayer quantum dots for potential application in near infrared light harvesting. (3rd May 2019) - Chatterjee, Arka; Das, Debabrata; Patwari, Jayita; Tongbram, Binita; Panda, Debiprasad; Chakrabarti, Subhananda; Pal, Samir Kumar
Abstract: Heterogeneously coupled self-assembled InAs QDs are always attractive to study their unique physical properties. Here, we have introduced Stranski-Krastanov (SK) grown InAs/GaAs QDs coupled to InAs/InGaAs submonolayer (SML) QDs to improve the light harvesting efficacy in the near infrared region (NIR) of the solar spectrum. Carrier migration mechanism from the SML stacks to the SK QDs and its dependence on the barrier thickness have been studied by temperature dependent steady state and picosecond resolved photoluminescence measurements. Both high and low energy excitations have been used to study the carrier migration and capture dynamics in the coupled heterostructures. It has been observed that the coupling is essentially determined by the spatial separation of both the QDs and the carrier lifetime reaches a maximum value at a certain barrier thickness. After successful optimization of the barrier thickness, we have used the SK-SML coupled structure as an active layer in a device to study its light harvesting efficacy. The SK-SML coupled device shows higher photocurrent, less saturation current and higher photovoltage compared to the uncoupled SK-QD one. In this study, we also find that the coupling in between the two classes of QDs increases the charge extraction efficiency and reduces the nonradiative recombination in the heterostructures. In brief, our experiments provide key information of the coupling mechanisms in the SK-SML coupled structure across various barrier thicknesses and its implication for improved device performance.